Chapter Effects of Water Scarcity on the Performances of the Agricultural Sector and Adaptation Strategies in Tunisia - Chebil, Ali (InTechOpen, 2019)
The chapter aims to develop a regionally disaggregated agricultural supply model for Tunisia in order to investigate the potential effects of increasing water scarcity on the performances of the agricultural sector in the country, and the structural adaptation strategies needed to face such a challenge. A set of scenarios combining future water availability, water use efficiency, and increasing producer prices were simulated using the developed model. Results show that the agricultural sector in Tunisia, particularly the agricultural employment, would be negatively affected in case of decreasing irrigation water availability, and mostly affected regions would be the north east, central west, and southern areas. However, it is always possible to mitigate such effects through a combination of structural adjustments (changing land use in different regions), enhanced water use efficiency, and support of producer prices. The model also provides recommendations regarding specific crops that should be promoted in specific regions in order to maintain an agricultural sector with high added value in Tunisia.